Evaluating the utility of routine screening catheterisation before interstage discharge of infants with single-ventricle physiology. (May 2019) - Bates, Katherine E.; Glatz, Andrew C.; Giglia, Therese M.; Natarajan, Shobha S.; Ravishankar, Chitra; Stagg, Alyson; Rome, Jonathan J.
Abstract: Introduction: Interstage mortality causes are often unknown in infants with shunt-dependent univentricular defects. For 2 years, screening catheterisation was encouraged before neonatal discharge to determine if routine evaluation improved interstage outcomes. Methods: Retrospective single-centre review of home monitoring programme from December, 2010 to June, 2012. Composite scores were created for physical examination/echocardiography risk factors; catheterisation risk factors; and interstage adverse events. Composite scores were compared between usual care and screening catheterisation groups. The ability of each risk factor composite to predict interstage adverse events, individually and in combination, was assessed with sensitivity, specificity, and receiver operating characteristic curves. Results: There were 27 usual care and 32 screening catheterisation patients. There were no significant differences between groups except rates of catheterisation before discharge (29.6 versus 100%, p < 0.001). Usual care patients who underwent catheterisation for clinical indications had higher intervention rates (37.5 versus 3.1%, p = 0.004). Physical examination/echocardiography risk factor frequency was similar, but usual care patients with catheterisation had a higher catheterisation risk factor frequency. Interstage adverse event frequency was similar (48.2 versus 53.1%, p = 0.7). For interstage adverse event prediction, sensitivity for the physical examination/echocardiography, catheterisation, and either risk factor composites was 53.3, 72, and 80%, respectively; specificity was 59, 60, and 48%. The area under the receiver operating characteristic curve was 0.56, 0.66, and 0.64. Conclusion: Screening catheterisation evaluation offered slightly increased sensitivity and specificity, but no difference in interstage adverse event frequency. Given this small advantage versus known risks, screening catheterisations are no longer encouraged.